2001
DOI: 10.1128/aem.67.9.4393-4396.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Nostoc Symbionts Endophytically Associated with Two Bryophyte Species

Abstract: The diversity of the endophytic Nostoc symbionts of two thalloid bryophytes, the hornwort Anthoceros fusiformis and the liverwort Blasia pusilla, was examined using the tRNA Leu (UAA) intron sequence as a marker. The results confirmed that many different Nostoc strains are involved in both associations under natural conditions in the field. The level of Nostoc diversity within individual bryophyte thalli varied, but single DNA fragments were consistently amplified from individual symbiotic colonies. Some Nosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 17 publications
3
37
0
2
Order By: Relevance
“…This is true both for sexual species with horizontal photobiont transmission (P. canina, P. membranacea, P. rufescens) and for species that produce specialized asexually derived codispersal propagules (P. didactyla). Sharing of photobiont genotypes among different host species has also been reported previously among members of the Nephromataceae (Rikkinen et al, 2002;Lohtander et al, 2003;Wirtz et al, 2003), as well as within bryophytes (Costa et al, 2001) and cycads (Costa et al, 1999), but ours is the first study to include large enough sample sizes of both plant symbionts and lichen photobionts to infer that symbiont sharing among unrelated hosts is common. These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000.…”
Section: Discussionmentioning
confidence: 81%
“…This is true both for sexual species with horizontal photobiont transmission (P. canina, P. membranacea, P. rufescens) and for species that produce specialized asexually derived codispersal propagules (P. didactyla). Sharing of photobiont genotypes among different host species has also been reported previously among members of the Nephromataceae (Rikkinen et al, 2002;Lohtander et al, 2003;Wirtz et al, 2003), as well as within bryophytes (Costa et al, 2001) and cycads (Costa et al, 1999), but ours is the first study to include large enough sample sizes of both plant symbionts and lichen photobionts to infer that symbiont sharing among unrelated hosts is common. These results contradict earlier studies, based on smaller datasets, which suggested that species-level host specialization was prevalent in cyanolichens and that host species was a better predictor of symbiont genotype than geography (Paulsrud et al, , 2000.…”
Section: Discussionmentioning
confidence: 81%
“…Apparently, this is second report for the isolation of Staphylococcus sp as endophytic bacteria (Stamford et al, 1998). The research with endophytic microorganisms is more focused in species with economic value such as corn, soy, grasses and others (Petrini, 1984;McInroy and Kloepper, 1995;Halmann et al, 1997;Naffaa et al, 1998;Araújo et al, 2000;Costa et al, 2001) or species capable of producing antimicrobials, as Taxus wallachiana (Yang et al, 1994). The method of the radial diffusion in solid media indicated the activity in qualitative form, directly correlating the diameters of the halo of degradation and the colony (Enzymatic Index) (Lin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria that live in the interior of plants without causing diseases to their hosts are called endophytic (Petrini et al, 1989;Azevedo et al, 2000). Endophytic microorganisms have been isolated from different types of vegetation such as grass (Naffaa et al, 1998), corn McInroy and Kloepper, 1995), Eriaceae (Petrini, 1984), cotton (McInroy and Kloepper, 1995), bryophytes (Costa et al, 2001), Solanum lycocarpum (Maitan, 1998) and agricultural crops (Halmann et al, 1997). Studies for the isolation and characterization of endophytic microorganisms of native plant specimens from Brazilian Cerrado biome are rare.…”
Section: Discussionmentioning
confidence: 99%
“…5 (Vance et al, 1998;Costa et al, 2001). Los heterocistos proporcionan los productos nitrogenados a las células vegetativas de la planta, y en turno reciben los productos fotosintéticos.…”
Section: Cianobacterias-briofitas (Musgos Hepáticas Y Antocerotas)unclassified